Mapping Global Research Trends on Sustainable Development Goals (SDGs): A Bibliometric Analysis using VOSviewer - Vika Puji Cahyani; Dewiyanti Fadly (Asian Journal of Environmental Research, 2026)
The Sustainable Development Goals (SDGs) provide a comprehensive global framework to address pressing social, economic, and environmental challenges. Despite the growing body of research, knowledge fragmentation and limited cross-disciplinary mapping hinder a holistic understanding of SDG research trends. This study aims to systematically map and analyze global SDG research developments from 2020 to 2026 using a bibliometric approach, with the 2025-2026 records treated as partial Scopus-indexed data rather than complete annual outputs. Data were retrieved from the Scopus database and processed with Publish or Perish, followed by scientific mapping in VOSviewer. The methodology included publication trend analysis, document-type distribution analysis, and keyword co-occurrence analysis to identify dominant research themes and emerging topics. A total of 186 publications were analyzed, revealing that comparable full-year research activity peaked in 2021-2022 and remained dominated by journal articles. Keyword analysis identified core clusters related to sustainable development, climate change, and food security, alongside emerging topics such as bioplastics, nanotechnology, low-carbon consumption, digital transformation, and sustainability education. These findings highlight both the evolution and diversification of SDG research, emphasizing the integration of technology, education, and practical applications. Understanding SDG research trends is essential for accelerating evidence-based environmental action, supporting climate mitigation strategies, and fostering interdisciplinary solutions to pressing ecological challenges such as biodiversity loss, pollution, and resource depletion. The study provides critical insights for researchers, educators, and policymakers to prioritize underexplored areas, foster cross-disciplinary collaborations, and guide evidence-based strategies for sustainable development.